2015
DOI: 10.1109/tnb.2015.2395143
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Method for Prediction of Saliva-Secretory Proteins and Its Application to Identification of Head and Neck Cancer Biomarkers for Salivary Diagnosis

Abstract: Human saliva is rich in proteins, which have been used for disease detection such as oral diseases and systematic diseases. In this paper, we present a computational method for predicting secretory proteins in human saliva based on two sets of human proteins from published literatures and public databases. One set contains known proteins which can be secreted into saliva, and the other contains the proteins that are deemed to be not extracellular secretion. The protein features with discerning power between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…The current study had some limitations. A number of methods have been developed to assess biomarkers in biological fluids to non‐invasively identify early HNSCC . Due to a lack of blood and/or saliva samples, we were unable to explore the diagnostic value of non‐invasive detection of HNSCC methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study had some limitations. A number of methods have been developed to assess biomarkers in biological fluids to non‐invasively identify early HNSCC . Due to a lack of blood and/or saliva samples, we were unable to explore the diagnostic value of non‐invasive detection of HNSCC methylation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of methods have been developed to assess biomarkers in biological fluids to non-invasively identify early HNSCC. 49,50 Due to a lack of blood and/ or saliva samples, we were unable to explore the diagnostic value of non-invasive detection of HNSCC methylation. In addition, emerging evidence indicates that a panel of several methylation genes could improve cancer diagnosis, 51 while our study focused on a single gene, which may not completely satisfy the requirements for clinical application.…”
Section: Hoxa9mentioning
confidence: 99%
“…Greater intensity in former smoker mean spectra shown efficacy for diagnosis [3,22,4]. In addition, studies have shown that the saliva content of the changes is closely related to the onset of oral diseases [2,23,24] and systemic diseases [2]. It is known that substances present in cigarettes, such as nicotine, can be detected in saliva [25], and this occurs because of the solubility properties of the agents present in cigarette smoke [26].…”
Section: Greater Intensity In Smoker Mean Spectramentioning
confidence: 99%
“…Saliva is a complex body fluid [1] that contains a large number of different types of proteins, hormones and ions [2]. It is secreted primarily by three pairs of salivary glands (parotid, submandibular and sublingual), as well as numerous minor salivary glands [2], With the continuous advancement of proteomics technology, salivary diagnosis has become a focus of several studies [2] and, mainly because besides being considered a fluid with excellent indicators of plasma levels of various substances [1] its collection is simple and noninvasive. Thus, saliva has been used for the early diagnosis, prevention, and monitoring process of various diseases [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al built a multi-classifier to predict various types of secreted proteins [ 15 ]. Besides simply predicting secreted proteins, Sun et al applied their method in the identification of head and neck cancer biomarkers [ 16 ]. Additionally, in secreted proteins, signal peptides are destined towards the secretory pathway [ 17 ].…”
Section: Introductionmentioning
confidence: 99%